Impact of Intravenous Tranexamic Acid on Intraoperative Bleeding during Endoscopic Sinus Surgery - Pawan Kumar Padhy; Ramakrishnan Narayanaswamy (Bengal Journal of Otolaryngology and Head Neck Surgery, 2019)
Introduction